Phenotype-based variation as a biomarker of sensitivity to molecularly targeted therapy in melanoma. Issue 1 (27th October 2016) - Senses, Kerem M.; Ghasemi, Mehdi; Akbar, Muhammad W.; Isbilen, Murat; Fallacara, Anna L.; Frankenburg, Shoshana; Schenone, Silvia; Lotem, Michal; Botta, Maurizio; Gure, Ali O.
Abstract : Transcriptomic phenotypes defined for melanoma correlate with sensitivity to MEK, SRC and HSP90 inhibitors. Abstract : Transcriptomic phenotypes defined for melanoma have been reported to correlate with sensitivity to various drugs. In this study, we aimed to define a minimal signature that could be used to distinguish melanoma sub-types in vitro, and to determine suitable drugs by which these sub-types can be targeted. By using primary melanoma cell lines, as well as commercially available melanoma cell lines, we find that the evaluation of MLANA and INHBA expression is as capable as one based on a combined analysis performed with genes for stemness, EMT and invasion/proliferation, in identifying melanoma subtypes that differ in their sensitivity to molecularly targeted drugs. Using this approach, we find that 75% of melanoma cell lines can be treated with either the MEK inhibitor AZD6244 or the HSP90 inhibitor 17AAG.